Characteristics of Wound Dressings and Dressings Based on Natural and Synthetic Polymers (Review Article) - B. A. Artikhodjaeva; Sh. S.Tashmukhamedova; Sh. S.Tashmukhamedova (Scholars Digest Publishing, 2023)
The article describes natural and synthetic polymeric materials used as the basis for the production of wound dressings. Methods for obtaining, stabilizing and sterilizing ready-made wound coverings, as well as the results of studies of antimicrobial and wound healing properties are considered.